(untitled) (Jurnal Teknologi (Sciences & Engineering), 2017)
Turbocharger is a device comprising mainly of a turbine and a compressor. The demand of turbocharger in the automotive industry increases as it significantly enhances the output power of an Internal Combustion Engine and reduces emission. The use of mixed flow turbine to replace the conventional radial turbine gives better impact since the turbine transient response increases and operates more efficiently at low velocity ratio. The flow behaviour inside the turbine affects the torque generation by the turbine. It is necessary for the turbine to have a specified clearance between the rotor tip and the casing of the turbomachine. This undoubtedly will contribute to clearance loss and mixing of leaked flow which produce disturbance to the exhaust flow. In order to investigate this effect, the validated Computational Fluid Dynamics method is chosen in order to replicate the flow field inside the mixed flow turbine. The simulation is carried out at the optimum operating condition which is at turbine total-to-static efficiency of 79% with inlet mass flow rate of 0.5kg/s. The flow inside the passage is plotted into pressure and velocity contours which are compared at 50% (30000rpm) and 80% (48000rpm) of the turbine design speed. The comparison between having 0% (no leakage) and 3% shroud tip clearance are then compared. Through the analysis, it is suggested that clearance leakage and flow separation cause disruption to the desirable uniform flow inside the turbine passage. The presence of Coriolis effect that resists the clearance leakage flow only at near leading edge of the rotor is observed. Furthermore, a low pressure region is perceived at rotor hub which absent in the radial flow turbine. These factors eventually reduce the performances of the actual turbine.